Islamic Banking in Indonesia: Assessing the Impact of Economic Turbulence and Market Dynamics on Credit Portfolios - Mubarok, Faizul; Wibowo, Martino; Utomo, Kabul Wahyu; Rahman, Saif Ur (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Indonesia’s Islamic banking sector has experienced rapid expansion in recent decades; however, credit growth within this sector remains volatile and insufficiently explored, particularly in relation to broader macroeconomic fluctuations. This study addresses this knowledge gap by investigating the key macroeconomic and financial determinants influencing credit growth in Islamic banks. It is driven by the need to understand how external shocks and policy variables affect Islamic financing behavior. Utilizing monthly data from 2002 to 2023, the study employs a Vector Error Correction Model (VECM), Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) to analyze both short- and long-term dynamics. The VECM results reveal a long-run equilibrium relationship between Islamic credit growth and macroeconomic indicators, including GDP, inflation, and interest rates. This finding suggests that Islamic credit, characterized by its unique Shariah-compliant principles, adjusts over time to restore equilibrium following disruptions. The IRF analysis further indicates that shocks to inflation and exchange rates tend to temporarily suppress credit growth, reflecting the sector’s sensitivity to price volatility and currency fluctuations. In contrast, positive shocks to GDP and stock market performance are associated with sustained increases in credit, underscoring the procyclical nature of Islamic bank lending. FEVD results show that GDP and inflation are the most significant drivers of credit growth variability, followed by interest rates and the exchange rate. These findings underscore that Islamic credit expansion is closely tied to real sector performance and overall macroeconomic stability. For policymakers and financial regulators, the study highlights the importance of maintaining sound macroeconomic fundamentals and fostering a stable investment climate. Such efforts are essential to support sustainable credit growth and enhance the resilience of Indonesia’s Islamic banking sector